Nanobodies: The "Magic Bullets" in therapeutics, drug delivery and diagnostics - Mir, Manzoor A; Mehraj, Umar; Sheikh, Bashir Ahmad; Hamdani, Syed Suhail (Human antibodies, 2020)
Antibodies represent a well-established class of clinical diagnostics for medical applications as well as essential research and biotechnological tools. Although both polyclonal and monoclonal antibodies are indispensable reagents in basic research and diagnostics but both of them have their limitations. Hence, there is urgent need to develop strategies aimed at production of alternative scaffolds and recombinant antibodies of smaller dimensions that could be easily produced, selected and manipulated. Unlike conventional antibodies, members of Camelidae and sharks produce antibodies composed only of heavy chains with small size, high solubility, thermal stability, refolding capacity and good tissue penetration in vivo. The discovery of these naturally occurring antibodies having only heavy-chain in Camelidae family and their further development into small recombinant nanobodies represents an attractive alternative in drug delivery, diagnostics and imaging. Nanobody derivatives are soluble, stable, versatile, have unique refolding capacities, reduced aggregation tendencies and high-target binding capabilities. They can be genetically customized to target enzymes, transmembrane proteins or molecular interactions. Their ability to recognize recessed antigenic sites has been attributed to their smaller size and the ability of the extended CDR3 loop to quickly penetrate into such epitopes. With the advent of molecular engineering and phage display technology, they can be of potential use in molecular imaging, drug delivery and therapeutics for several major diseases. In this review we present the recent advances in nanobodies for modulating immune functions, for targeting cancers, viruses, toxins and microbes as well as their utility as diagnostic and biosensor tools.